The role of targeted therapy in thymic carcinoma. (October 2019) - Krishnan, Mridula; Ganti, Apar K
Thymic carcinoma is a rare entity and can be distinguished from benign thymomas by their aggressive nature and poor prognosis. The National Comprehensive Cancer Network guidelines recommend resection followed by adjuvant platinum-based chemotherapy for resectable tumors. However, the outcomes for metastatic or relapsed thymic carcinomas are poor with no regimen showing a consistent benefit. Moreover, the relative rarity of these tumors makes clinical trials difficult. Molecular analysis of thymomas shows a high incidence of genetic mutations and targeted therapy holds promise. We will briefly outline and review the current role of targeted therapy in thymic cancer.